Behavioral differences between infants at and not at elevated risk for autism during a contingency paradigm - Marcelo R. Rosales; José Carlos Pulido; John Sideris; Grace T. Baranek; Nina S. Bradley; Maja Matarić; Beth A. Smith (PLoS ONE, 2026)
Introduction Motor impairments have been reported in infants at elevated likelihood of autism and those later diagnosed with autism. However, empirical studies comparing higher to lower likelihood infants are lacking, limiting our understanding of these motor impairments. This study aimed to determine and describe the behavioral differences between infants at higher (HLA) versus lower likelihood (LLA) of autism during a contingency learning paradigm. Methods Thirty full-term infants (6–9 months of age) at HLA and LLA (n = 15 per group) participated in a contingency learning paradigm. Movements of the infant’s right leg activated an infant-sized humanoid robot to reinforce production of right leg movements. Gaze behaviors, the number of times the infants activated the robot, and evidence supporting learning were examined and compared between groups. Results Gaze and motor behavioral data suggest no discernable group differences in terms of overall looking duration, anticipatory gazes, and number of robot activations. However, four of the infants at HLA displayed visual motor patterns that were qualitatively different. Conclusion Results from our study suggest that infants at HLA and LLA are using similar behaviors to learn a contingency learning task, but heterogeneity within the HLA group is noted and requires further study.